Flexible pressure sensor based on graphene aerogel microstructures functionalized with CdS nanocrystalline thin film. (May 2018) - Plesco, Irina; Dragoman, Mircea; Strobel, Julian; Ghimpu, Lidia; Schütt, Fabian; Dinescu, Adrian; Ursaki, Veaceslav; Kienle, Lorenz; Adelung, Rainer; Tiginyanu, Ion
Abstract: In this paper, we report on functionalization of graphene aerogel with a CdS thin film deposited by magnetron sputtering and on the development of flexible pressure sensors based on ultra-lightweight CdS-aerogel nanocomposite. Analysis by scanning electron microscopy, transmission electron microscopy and energy dispersive X-ray analysis disclose the uniform deposition of nanocrystalline CdS films with quasi-stoichiometric composition. The piezoresistive response of the aforementioned nanocomposite in the pressure range from 1 to 5 atm is found to be more than one order of magnitude higher than that inherent to suspended graphene membranes, leading to an average sensitivity as high as 3.2 × 10 −4  kPa −1 . Graphical abstract: Image 1 Highlights: Technology for the functionalization of graphene aerogel with a CdS thin film has been developed. An ultra-lightweight flexible CdS-graphene aerogel nanocomposite was produced. Crystallinity of the graphene and CdS components of nano/microstructures is demonstrated. The piezoresistive response of the nanocomposite is more than ten times higher than that of graphene membranes. A pressure sensor with sensitivity as high as 3.2 × 10 −4  kPa −1 in the pressure range from 1 to 5 atm has been developed.